2009
DOI: 10.1108/09590550910999343
|View full text |Cite
|
Sign up to set email alerts
|

Consumer‐factors moderating private label brand success: further empirical results

Abstract: 2 Consumer-factors Moderating Private Label Brand Success: Further Empirical Results AbstractPurpose-This research examines the category-level differences of both risk perception and brand loyalty effects on consumer proneness towards buying private label brands (PLBs).Methodology/Approach-This study extends the work of Batra and Sinha (2000) (B&S) by also examining the PLB effects of brand loyalty and price-quality by product category using a mallintercept survey. Findings-The results indicate that quality va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 49 publications
3
62
0
3
Order By: Relevance
“…This information is derived from a multitude of sources, including traditional advertising (Arens et al, 2012;Yang et al, 2005;Agrawal, 1996), word of mouth correspondence with friends, family and colleagues (Trusov et al, 2008;Allsop et al, 2007;Brown et al, 2007), as well as actual experience of using the brand (Glynn and Chen, 2009;Erdem and Swait, 1998). These ongoing phenomena supplement the influences that consumers experience in an instore environment.…”
Section: The Role Of Familiarity With Private Label Brandsmentioning
confidence: 95%
See 1 more Smart Citation
“…This information is derived from a multitude of sources, including traditional advertising (Arens et al, 2012;Yang et al, 2005;Agrawal, 1996), word of mouth correspondence with friends, family and colleagues (Trusov et al, 2008;Allsop et al, 2007;Brown et al, 2007), as well as actual experience of using the brand (Glynn and Chen, 2009;Erdem and Swait, 1998). These ongoing phenomena supplement the influences that consumers experience in an instore environment.…”
Section: The Role Of Familiarity With Private Label Brandsmentioning
confidence: 95%
“…Furthermore, consumers who exhibit brand loyalty to a particular brand usually develop a habit of purchasing said brand, due to an emotional attachment as well as satisfaction related to previous purchases of the brand (Lim and Razzaque (1997) as cited in Glynn and Chen (2009)). A further rationale for the differing loyalty to NBs and PLBs surrounds the extrinsic cues related to distribution (Glynn and Chen, 2009). NBs experience greater distribution intensity, whereas PLBs, by their very nature, are only available in particular stores (Glynn and Chen, 2009).…”
Section: The Moderation Effect Of Pre-existing Loyalty Towards Nationmentioning
confidence: 98%
“…Batra and Sinha (2000) found that store brand buying increases when overall risk perception declines. The higher the perceived risk associated with the PL purchase, the lower the PL proneness (Glynn and Chen 2009).…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…The studies done by Raza & Rehman (2012); Jabbar & Baldwin (2010) reveal that perceptions can be influenced by the association of brand with images of the product. According to Glynn & Chen (2009); perception of a product's quality is one of the most important elements for a brand and quality can be combined with prompts.…”
Section: Product Brandingmentioning
confidence: 99%